Містечко Браїлів у період Української революції 1917-1920 рр. - Романюк, І.М.; Смірнов, М.А. (Сумський історико-архівний журнал, 2010)
Social-political changes in the town of Brayiliv (Vinnytsa region) during the period of revolutionary events in 1917-1920 are examined in the article.